Pengaruh Energi Gelombang Laut Terhadap Turbin Penggerak Listrik - Anggraeni, Diva Kanaya; Yushardi, Yushardi; Sudarti, Sudarti (Peneliti.net, 2024)
Indonesia has a lot of great potential that can help human resources in carrying out daily activities, especially in the maritime sector, which is very broad and large, measuring almost ± 6,000,000 km2. Unfortunately, the utilization of air wave energy has not been fully utilized optimally and several researchers have not carried out much research regarding the electrical energy formed from sea waves. The government has a policy to facilitate researchers' interest in conducting research so that there are many numerical specifications for the energy potential of ocean currents in turbine trials. There has been research into turbine trials at sea since 2006. Current turbines are an alternative energy source from kinetic energy to electrical energy. This research was carried out using a qualitative descriptive method, namely research that can describe the results that have been obtained by several studies that have been carried out previously. So far, the resources used by humans to generate electricity mostly use non-renewable resources such as fossil fuels (petroleum and coal).